Pregnenolone-methyl-ether enhances CLIP170 and microtubule functions improving spine maturation and hippocampal deficits related to CDKL5 deficiency. Issue 16 (25th March 2022) - Barbiero, Isabella; Zamberletti, Erica; Tramarin, Marco; Gabaglio, Marina; Peroni, Diana; De Rosa, Roberta; Baldin, Serena; Bianchi, Massimiliano; Rubino, Tiziana; Kilstrup-Nielsen, Charlotte
Abstract: Mutations in the X-linked cyclin-dependent kinase-like 5 ( CDKL5 ) cause CDKL5 deficiency disorder (CDD), a neurodevelopmental disease characterized by severe infantile seizures and intellectual disability. The absence of CDKL5 in mice causes defective spine maturation that can at least partially explain the cognitive impairment in CDKL5 patients and CDD mouse models. The molecular basis for such defect may depend on the capacity of CDKL5 to regulate microtubule (MT) dynamics through its association with the MT-plus end tracking protein CLIP170 (cytoplasmic linker protein 170). Indeed, we here demonstrate that the absence of CDKL5 causes CLIP170 to be mainly in a closed inactive conformation that impedes its binding to MTs. Previously, the synthetic pregnenolone analogue, pregnenolone-methyl-ether (PME), was found to have a positive effect on CDKL5-related cellular and neuronal defects in vitro . Here, we show that PME induces the open active conformation of CLIP170 and promotes the entry of MTs into dendritic spines in vitro . Furthermore, the administration of PME to symptomatic Cdkl5 -knock-out mice improved hippocampal-dependent behavior and restored spine maturation and the localization of MT-related proteins in the synaptic compartment. The positive effect on cognitive deficits persisted for 1 week after treatment withdrawal. Altogether, our results suggest that CDKL5 regulates spine maturation and cognitive processes through its control of CLIP170 and MT dynamics, which may represent a novel target for the development of disease-modifying therapies.